1991
DOI: 10.1152/ajpendo.1991.260.3.e447
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ca influences vitamin D metabolite levels as rats develop vitamin D deficiency

Abstract: The hypocalcemia that accompanies vitamin D deficiency is a major obstacle to proper interpretation of the role(s) of vitamin D metabolites in Ca-sensitive tissues. This paper describes the development and complete characterization of a dietary regimen with which normocalcemia was maintained in rats throughout the development of vitamin D deficiency. Normal weanling rats were fed diets containing 0.8% Ca, 0.5% P, and vitamin D3 (group A), or vitamin D-deficient diets containing 0.8% Ca and 0.5% P (group B); 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
2
13
1
Order By: Relevance
“…2a, b, &c). Since the vitamin D content in the regular rat chows which contain 2.2 IU/g vitamin D [33] is comparable to our special 2 IU/g diet, apparently, the normal level of vitamin D in the diet or normal circulating level [33] of 25(OH)D may not be sufficient for preventing ICC tumor initiation and progression (Fig. 2a, b, &c).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…2a, b, &c). Since the vitamin D content in the regular rat chows which contain 2.2 IU/g vitamin D [33] is comparable to our special 2 IU/g diet, apparently, the normal level of vitamin D in the diet or normal circulating level [33] of 25(OH)D may not be sufficient for preventing ICC tumor initiation and progression (Fig. 2a, b, &c).…”
Section: Discussionmentioning
confidence: 88%
“…1b and 1c). This observation, showing no adverse effects on body weight and serum calcium, indeed indicates that supplementation with 6 IU/g of vitamin D 3 did not cause unwanted side-effects even though they had serum 25(OH)D higher than the normal range [33]. Furthermore, the lack of increase in serum calcium in 6 IU/g group demonstrates that any anti-ICC effects observed in this group are most likely a direct consequence of vitamin D supplementation, and not a secondary effect attributable to calcium [34, 35].…”
Section: Discussionmentioning
confidence: 88%
“…The active metabolite has many functions related to Ca regulation and bone metabolism, including intestinal Ca and P absorption, Ca mobilization in the bone, and resorption of P and Ca in the renal tubular cells (Deluca 2004;Jones et al 1998;Lips 2006). Although vitamin D interacts with PTH (Deluca 2004;Jones et al 1998), hypovitaminosis D does not influence PTH under sufficient serum levels of Ca (Dabbagh et al 1989;Kollenkirchen et al 1991), and many researchers (Fox 1992;Lee et al 1991;Masuyama et al 2003) have reported a vitamin D-independent Ca homeostasis system. Therefore, hypovitaminosis D alone might not affect Ca homeostasis and bone remodeling owing to the vitamin D-independent system in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This dietary regimen results in ϪD with normocalcemia after 6-8 wk, which is sustained for at least 4-5 mo (26,27). In these studies, rats were maintained on the ϪD diet for 7 wk-5 mo before hor-…”
Section: Animalsmentioning
confidence: 99%